The Evaluation of Resistant Level of Ty-2gene on Chromosome 11 to Tomato Yellow Leaf Curl Virus at BC6F2 Generation between a Cross of Wild Species Tomato, Solanum habrochaites Accession ‘L06112’ Clone No.1 and Commercial Cultivar, Seedathip3 in 3 Locations - Chomdej, Ornubol Chomdej; Sinbunyama, Itsarayot; Pongpayaklers, Uraiwan; Juejun, Narisa (Thai Journal of Science and Technology, 2022)
Tomato yellow leaf curl disease is one of the diseases that cause damage to commercial tomato cultivars in every region of Thailand. The Seedathip3 tomato cultivar was used for introgression of TYLCV resistance genes from a wild species, Solanum habrochaites L06112 accession. Tomato seedlings from the BC6F2 generation were verified by 3 positions of DNA markers for containing a major resistance gene on chromosome 11. The BC6F2 generations were tested for TVLCV resistance at 3 locations with different viral isolations. The locations included; TYLCTHV-[NP] at TVRC Kasetsart University, Nakhon Pathom province, TYLCTHV-[CM] at East West Seed Company Suphanburi province, and TYLCTHV-[NK] at Syngenta Company Khon Kaen province. Different inoculation methods were used at each of the three locations. Symptom observations were recorded every week for 7 weeks. The viral concentrations were checked at 7 weeks post-inoculation. The resistance line, S. habrochaites showed complete resistance at 3 locations with the highest disease score at 0.3 and ELISA readings with presence lower than the cut-off value, while Seedathip3 showed susceptibility at all 3 locations with disease scoring of 2.48-3.06. The F1 generation of Seedathip3 and S. habrochaites showed disease scores in the range of 0.73-1.5. The BC6F2 results showed susceptibility with disease scores higher than F1 generation at all locations. This is the result of only the Ty-2 selection on chromosome 11. S. habrochaites have another gene that affects the mechanism of TYLCV resistance. The commercial tomato cultivars require resistant gene combinations to improve the level of TYLCTHV resistance.